PENGEMBANGAN “FUNCTION MOBILE: FRACTION SERIES” UNTUK PENGENALAN KONSEP BILANGAN PECAHAN [DEVELOPMENT OF “FUNCTION MOBILE: FRACTION SERIES” FOR INTRODUCTION TO FRACTIONAL NUMBER CONCEPTS] - Elvaretta, Nathania Dea; Setyadi, Danang (Universitas Pelita Harapan, 2025)
Students' low understanding of the concept of fractions is often caused by the abstract nature of the material and the use of conventional learning media that are less interesting. The development of learning media nowadays needs to be adjusted to the ability of students who are capable of using smartphones as learning tools. Therefore, the purpose of this research is to create Android-based math learning media that can help third-grade elementary school students in recognising fractions. This learning media is in the form of an Android game named